2018
DOI: 10.31086/tjgeri.2018240428
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Homes Nurses Attitudes Toward Older People and Affecting Factors

Abstract: Materials and Method:A retrospective medical record review of geriatric patients aged ≥65 years (Group G, n=185) who had undergone outpatient inguinal hernia repair under local infiltration anesthesia (LIA) and sedation was conducted. Their data were compared with those of a group of nongeriatric patients aged 18-64 years (Group C, n=185). Patient selection, anesthetic and surgical care, and discharge criteria were protocol-based. Safety was evaluated in terms of incidence of adverse events, discharge delay, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Students' attitudes and views towards long-term care varied depending on their own expectations, experiences and perceptions. Students sense the atmosphere at the ward, the manner of interactions withward staff [28][29][30]58], nurses' attitudes towards older adults [26] and their willingness to attend to older adults' needs [1]. Students observe matters in different manners and consider different things meaningful, depending on their previous experiences or assumptions, current learning needs and expectations for the future.…”
Section: Examination Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students' attitudes and views towards long-term care varied depending on their own expectations, experiences and perceptions. Students sense the atmosphere at the ward, the manner of interactions withward staff [28][29][30]58], nurses' attitudes towards older adults [26] and their willingness to attend to older adults' needs [1]. Students observe matters in different manners and consider different things meaningful, depending on their previous experiences or assumptions, current learning needs and expectations for the future.…”
Section: Examination Of the Resultsmentioning
confidence: 99%
“…The quality of nursing care in nursing homes is closely related to nurses' attitudes towards older adults. Nurses working in nursing homes showed only slightly positive attitudes towards older adults [26]. A study by Dahlke et al [1] found that nursing staff do not listen to older patients or attend to their needs.…”
Section: Introductionmentioning
confidence: 99%
“…Attitudes and perceptions of nurses, who have a key role in elderly care, affect the quality of care (Wanko et al, 2021). In studies conducted by Akpinar et al reported in the literature that nurses' attitudes towards the elderly are positive and negative (Akpinar et al, 2018). However, it has been observed that studies qualitatively evaluating nurses' perception and thoughts of the ageing, difficulties that they faced in older care are limited (Lennox et al, 2019).…”
Section: Introductionmentioning
confidence: 99%